Defected red blood cell membranes and direct correlation with the uraemic milieu: the connection with the decreased red blood cell lifespan observed in haemodialysis patients - Stamopoulos, D.; Grapsa, E.; Manios, E.; Gogola, V.; Bakirtzi, N. (NANOTECHNOLOGY, 2012)
Together with impaired production of erythropoietin and iron deficiency, the decreased lifespan of red blood cells (RBCs) is a main factor contributing to the chronic anaemia observed in haemodialysis (HD) patients. Atomic force microscopy is employed in this work to thoroughly survey the membrane of intact RBCs (iRBCs) of HD patients in comparison to those of healthy donors, aiming to obtain direct information on the structural status of RBCs that can be related to their decreased lifespan. We observed that the iRBC membrane of the HD patients is overpopulated with extended circular defects, termed 'orifices', that have typical dimension ranging between 0.2 and 1.0 mu m. The 'orifice' index-that is, the mean population of 'orifices' per top membrane surface-exhibits a pronounced relative increase of order 54 +/- 12% for the HD patients as compared to healthy donors. Interestingly, for the HD patients, the 'orifice' index, which relates to the structural status of the RBC membrane, correlates strongly with urea concentration, which is a basic index of the uraemic milieu. Thus, these results indicate that the uraemic milieu downgrades the structural status of the RBC membrane, possibly triggering biochemical processes that result in their premature elimination from the circulation. This process could decrease the lifespan of RBCs, as observed in HD patients.